Nomograms for the Administration of Unfractionated Heparin in the Initial Treatment of Acute Thromboembolism – an Overview - Bernardi, Enrico; Piccioli, Andrea; Oliboni, Giancarlo; Zuin, Renzo; Girolami, Antonio; Prandoni, Paolo (Thrombosis and Haemostasis, 2000)
Despite the availability of low-molecular-weight heparins, unfractionated heparin (UFH) still remains the drug of choice for the initial treatment of acute venous thromboembolism in many countries. When appropriately employed, UFH treatment results in a degree of efficacy and safety that is fully comparable with that obtained with the use of heparin derivatives. The use of nomograms for the intravenous or subcutaneous administration of UFH assures that virtually all patients will promptly achieve adequate levels of anticoagulation, thus decreasing the likelihood of recurrent venous thromboembolism without extra bleeding-risk.In this article we reviewed clinical studies on the implementation and validation of UFH dosing nomograms, and attempted a quantitative analysis of their performance. According to the results of our analysis, a statistically significantly higher proportion of patients treated on the basis of a nomogram reached a therapeutic anticoagulant level within 24 h of treatment, as compared to patients treated following the standard practice (odds ratio, 3.6; 95% CI, 2.6 to 4.9). The rate of recurrent thromboembolic events was significantly lower for patients treated according to a nomogram (odds ratio, 0.3; 95% CI, 0.1 to 0.8), while no significant differences in terms of either major or minor bleedings were detected between nomogram patients and controls.
Keywords: Overview; unfractionated heparin; thromboembolism (acute); nomogram(s)